Penerapan Kompres Hangat Elektrik dan Relaksasi Nafas dalam terhadap Tingkat Nyeri Dismenore pada Remaja Putri di SMK Negeri 1 Sragen - Devia Riza Maharani; Hermawati Hermawati (NAJ Nursing Applied Journal, 2024)
Background: Dysmenorrhea pain is lower abdominal pain that can spread the lower back, waist, pervis, caused contractions uterine muscles when blood released from the uterus, causing the muscles highten and causing pain and cramps. The incidence rate in Indonesia 64,25% divided primary dysmenorrhea 54,89% and secondary dysmenorrhea 9,36%. Warm compresses have the body’s response heat which causes dilation of blood vassels wich improves blood circulation. Deep breathing relaxation through breathing exercises stimulates body form pain suppression system, wich ultimately can reduce pain intensity. Objective : Describe the results before and after administering warm electric compresses and deep breathing relaxation on the level of dysmenorrhea pain. Method: Case study method by observing pain levels and using the Numeric Rating Scale (NRS) measuring scale. Results: There was reduction dysmenorrhea pain both respondents after giving warm compresses electric and deep breathing relaxtion to Nn. R a scale of 6 to 4 and Nn. A a scale of 8 to 5. Conslusion: Applying warm compresses and deep breathing relaxation young women with dysmenorrhea pain can reduce the level of pain.